Protection of children’s rights in schools of Uzbekistan: theoretical and practical approaches - Asadova, Mohinabonu Akbarovna (The Lingua Spectrum, 2026)
This article analyzes the theoretical and practical foundations of protecting children’s rights in schools of Uzbekistan. The purpose of the study is to identify pedagogical and legal mechanisms for ensuring children’s rights to education, a safe learning environment, non-discrimination, freedom of expression, and psychological support. The methods include analysis of legal documents, pedagogical literature, international standards, and school-based practices. The results show that effective protection of children’s rights depends on legal culture, inclusive education, psychological safety, teacher competence, and cooperation among school, family, and society. The discussion addresses existing challenges, including traditional pedagogical approaches, insufficient psychological services, weak parental involvement, bullying, and digital safety risks. The conclusion emphasizes that protecting children’s rights is essential for improving education quality and supporting democratic social development. The recommendations proposed in the article may help strengthen legal education, safe school environments, inclusive practice, and child-centered pedagogy in general education institutions.